Gen-Z's Perception of Self-Development Lifestyle Towards Marriage Interest Islamic Family Law Perspective - Ayu Novita Puasari; Gandhi Liyorba Indra; Syarif Bahaudin Mudore (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The 20.67% decline in the number of marriages in Indonesia between 2018 and 2024 indicates a shift in views among Gen-Z. This study aims to analyze the influence of a self-improvement lifestyle on interest in marriage among Gen-Z and evaluate this phenomenon from the perspective of Islamic Family Law. The research method used was qualitative with a phenomenological approach. Information was obtained through interviews and questionnaires distributed to students at Raden Intan State Islamic University, Lampung. The research findings indicate that a self-improvement lifestyle has a significant impact on Gen-Z's interest in marriage, with most respondents choosing to focus on careers, education, and financial independence. The main factors influencing this reduced interest are concerns about limited personal freedom, obstacles to self-actualization, and the desire to achieve emotional maturity before marriage. From the perspective of Islamic Family Law, this phenomenon of delayed marriage is considered a precautionary measure to prepare physically and mentally. Islam does not require marriage to be carried out hastily if it is feared that the goals of a marriage that is sakinah, mawaddah, and rahmah will not be achieved. This study found that for Gen-Z, self-development is not just a trend, but a foundation that is considered important to prepare before starting family life in the modern era.